Control of nozzle flow using microjets at supersonic Mach Regime - G M, Fharukh; Khan, Sher Afghan (Materials and Energy Research Center, 2019)
This article reports the active control of base flows using the experimental procedure. Active control of base pressure helps in reducing the base drag in aerodynamic devices having suddenly expanded flows. Active control in the form of microjets having 0.5 mm radius placed at forty-five degrees apart is employed to control the base pressure. The Mach numbers of the present analysis are 1.7, 2.3, and 2.7. The length to diameter (L/D) ratio is varied from 10 to 1 and the nozzle pressure ratio (NPR) being changed from 1 to 10 in steps of 1 for base pressure measurements. The area ratio for the entire analysis is fixed at 2.56. Wall pressure distribution along the enlarged duct is also recorded. No change in base pressure increase/decrease is thoroughly analyzed as well. From the experimental investigation, it is found that control plays an important in modifying the base pressure without disturbing the wall pressure distribution. The base pressure variation is entirely different at L/D = 1 compared to a higher L/D ratio due to change in reattachment length and the requirement of the duct length at higher inertia levels. The quality of the flow in the duct in the presence and absence of control remained the same.